Investigating the protective contribution of PLCG2 P522R variant in microglia‐mediated immune pathways in Alzheimer's Disease. (20th December 2022) - Liang, Xinyan
Abstract: Background: As the main innate immune cell in central nervous system (CNS), microglia plays an indispensable roles in neuroinflammation and neurodegenerative diseases, such as Alzheimer's Disease (AD). Large scale population studies have identified an AD‐associated rare coding variant in the Phospholipase C Gamma 2 (PLCG2) locus (rs72824905, P522R, P =5.38x10 ‐10, odds ratio = 0.68), which potentially offers protection against AD. This variant is associated with lower Aβ1‐42 and pTau181 levels in patients, as well as delays cognitive decline in mild cognitive impairment (MCI) progression. It has been reported that PLCG2 highly expresses in microglia in CNS and mainly involved in immune response, therefore, PLCG2 P522R variant may be a central player in the microglial‐mediated immune pathways during AD pathogenesis. Method: We generated a PLCG2 522R/R knock‐in mouse model carrying this human variant with CRISPR‐mediated gene editing. To explore the protective nature of PLCG2 P522R variant, we generated PLCG2 522R/R ; 5XFAD mouse model by crossing PLCG2 522R/R knock‐in model with the 5XFAD mice, and accessed major AD phenotypes including Aβ load and microgliosis in vivo . Result: Our data showed that PLCG2 522R/R ;5XFAD mice exhibited attenuated AD pathologies compared with PLCG2 522P/P ;5XFAD mice, including less burden of Aβ in cortical and hippocampal regions, and less Aβ‐associated microglia clustering around Aβ plaques at early stage of AD. Conclusion: PLCG2 P522R variant can protect against AD pathology in PLCG2 522R/R ;5XFAD mice, which may likely link to its hypermorphic effect in immune pathways, so that PLCG2 522R/R microglia potentially have improved phagocytotic function and restrict Aβ accumulation in brain. We believe that investigating the protective role of PLCG2 P522R mutation may help us better understand the neuroinflammation aspect of AD pathogenesis, and provide new strategies to developing clinical therapy in the future.